THE ROLE OF SEARCH ENGINE OPTIMIZATION IN INFLUENCING PSYCHOLOGICAL FACTORS IN PURCHASING BEHAVIOR CONSUMER - Rissa Hanny; Heri Nurranto; M. Alimardi Hubeis; Mohamad Rizan; Setyo Ferry Wibowo (JIM : Journal Of International Management, 2025)
This study explores the influence of Search Engine Optimization (SEO) on consumer psychological behavior and purchasing decisions within the digital marketing landscape. Drawing from a meta-synthesis of 50 peer-reviewed articles published between 2019 and 2024, the research highlights how on-page, off-page, and technical SEO On-page SEO elements, such as keyword optimization and content structure, are shown to enhance cognitive fluency and relevance, while off-page strategies, including backlinks and social signals, bolster brand credibility and social validation. Technical SEO factors, such as site speed and mobile responsiveness, foster user comfort and perceived trust. The study also incorporates psychological frameworks like the Theory of Planned Behavior (TPB) and the Stimulus-Organism-Response (S-O-R) model to analyze how SEO functions as both a technical and behavioral influence mechanism. The findings underscore the strategic importance of SEO in optimizing the consumer journey, from awareness to conversion, and suggest directions for future research that emphasize cultural, neurocognitive, and experimental perspectives.